A Novel Thermochemical Long Term Storage Concept: Balance of Renewable Electricity and Heat Demand in Buildings - Schmidt, Matthias; Linder, Marc (Frontiers in Energy Research, 2020)
Until today the space heat demand of residential buildings in northern and middle European countries is still mainly supplied by the combustion of fossil fuels (mostly gas and oil). The sector therefore contributes a major share of the yearly energy related CO2 emissions of these countries. One reason for the low renewable penetration in the heating sector is, that the largest heat demand occurs during the winter period whereas in contrast high production rates of renewables prevalently occur during the summer period. To overcome this seasonal discrepancy this paper proposes a novel long term storage system based on the thermochemical reaction of calcium hydroxide to calcium oxide and water. Basic idea of the concept is to use excess electricity, for example from roof top photovoltaic systems, during the summer time to drive the endothermal charging reaction. The charged material can then be stored in simple containers at ambient temperature and the chemical potential is preserved without energy losses for an unlimited period of time. During the winter the thermal energy, which is released by performing the exothermal back reaction, provides the heat demand of the building. In contrast to so far analysed reaction systems for seasonal storage, the system is discharged with liquid water instead of water vapour, which enhances the discharging process, technically and energetically. Moreover using electrical energy for charging, instead of solar thermal energy, allows a flexible adaption of the storage operational times. This way, the system can be operated so, that the waste heat, which necessarily occurs during the charging process, can completely be used to satisfy the domestic hot water production during the summer. This newly identified operation principle enables a significant increase of the systems storage efficiency. A detailed analysis of the energy balance combined with a first case study of the integration into the building revealed that a potential storage efficiency of up to 96 % can be reached. In brief, this paper presents a completely new technological concept which couples the power and heat sector by cost efficient long term energy storage and evaluates the potential for the application in residential buildings.